Generating a consensus on an undergraduate curriculum for paediatric caries management: a protocol for a Delphi and nominal groups study - Helen J. Rogers; Faith Campbell; Nicola Innes (BMC Medical Education)
Abstract Background Untreated dental caries is the most common condition to affect children globally, and significantly affects their oral health-related quality of life. Our understanding of caries and its management has progressed significantly over the past two decades, though a number of Dental Schools in the United Kingdom (UK) continue to teach traditional techniques, which no longer align with the evidence base. There is a clear need for an evidence-based curriculum for paediatric caries management for UK Dental Schools. This protocol details a study to generate consensus on what should be included in such a curriculum. Methods Preliminary research by the authors will be used to identify techniques to be considered for inclusion in the curriculum and their definitions will be drawn from scientific literature. A total of 21 national and international experts in paediatric cariology will be invited to take part in a Delphi survey, via the Welphi application. Participants will be given a list of techniques, with associated definitions, and asked to state whether each should be included in the curriculum, or not, or if they are unsure. Techniques with at least 70% agreement will be removed from future survey rounds. Participants will be provided with feedback regarding all techniques not reaching a consensus, and asked to re-evaluate these again, up to a maximum of four rounds. Seven UK-based Delphi participants will then be invited to participate in a Nominal Group Technique approach, to confirm suitability of the techniques agreed for inclusion in a UK curriculum, reviewing and discussing where agreement was previously not reached. The final list of approved techniques will inform a UK paediatric caries management curriculum, which will be developed with involvement of stakeholders. Endorsement for this curriculum will be sought from the British Society of Paediatric Dentistry. The UK General Dental Council will be asked to consider its content as part of the standards for UK Dental Schools. Following dissemination of the curriculum we will seek to investigate whether there is greater alignment across UK Dental Schools with the evidence base for cariology. Conclusion This study proposes a rigorous approach to curriculum development with active involvement of a broad range of stakeholders. These methods can be applied to development of further curricula in dental education, benefitting the teaching community, students and patients.